Simulation Game-Based Governance System Education - Glenn Hariyanto Putra; Erdhi Widyarto Nugroho; T.Brenda Chandrawati (Journal of Business and Technology, 2023)
Democratization is a process of people's participation in the country's political activities, but this process is quite difficult because the public's perception of the government tends to be negative. One way to increase public awareness about government is to use educational games such as "Governman" which teach about the government system through simulation and make players think critically and creatively. The game "Governman" is made using the waterfall method and has gone through all the stages in that method. Research has been conducted to show that this game is effective in encouraging the player's intention to learn about the government system. It is hoped that this game will be an interesting and easy-to-understand way for players to learn about the government system. Research has been conducted to evaluate the effectiveness of this game and the results show that this game has a valid correlation between Performance Expectancy, Effort Expectancy, Hedonic Motivation and Behavioral Intention. This shows that this game is effective in encouraging players' intentions to learn and understand the government system